1979
DOI: 10.1093/ajcn/32.10.2115
|View full text |Cite
|
Sign up to set email alerts
|

Assessing iron status of a population

Abstract: Reliable methods for assessing the iron status of a population are essential for developing effective public health measures to combat iron deficiency. The hemoglobin concentration, transferrin saturation, free erythrocyte protoporphyrin, and serum ferritin are all useful but they vary widely in their specificity and sensitivity for detecting iron deficiency. In applying these laboratory parameters, the usual approach in nutritional surveys is to determine the percentage of values outside the normal range. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
161
1
19

Year Published

1984
1984
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(191 citation statements)
references
References 12 publications
10
161
1
19
Order By: Relevance
“…This is most probably due to the use of different standards (9). The separation between patients and healthy control subjects was better for the iron-overload patients than for the iron-deficient anemia patients, which is in harmony with the prevalence of these disorders in the population (19)(20)(21). In contrast to men and postmenopausal women, serum ferritin concentrations in younger women were found to be close to those in iron-deficient anemia patients.…”
Section: Discussionmentioning
confidence: 66%
“…This is most probably due to the use of different standards (9). The separation between patients and healthy control subjects was better for the iron-overload patients than for the iron-deficient anemia patients, which is in harmony with the prevalence of these disorders in the population (19)(20)(21). In contrast to men and postmenopausal women, serum ferritin concentrations in younger women were found to be close to those in iron-deficient anemia patients.…”
Section: Discussionmentioning
confidence: 66%
“…In such contexts, no single measurement when used alone may be considered specific enough to identify ID (5,6,32) . As suggested in other studies (33,34) , in the current research ID was defined by at least two abnormal values among the three parameters of Fe status used. According to this multiple criteria model, we found that almost 32 % of the adolescent girls were Fe-deficient which is similar to the prevalence seen among menstruating women from Côte d'Ivoire (35 %) (20) .…”
Section: Discussionmentioning
confidence: 92%
“…As no single indicator reflects the entire spectrum of iron status (Cook et al, 1976), we used a common multiple biochemical test strategy (Yip et al, 1984;Expert Scientific Working Group, 1985;English & Bennett, 1990;Preziosi et al, 1994). Our model included SF, TfS and Hb.…”
Section: Venous Blood Samplesmentioning
confidence: 99%